Study Effect of Organizational Characteristics on Coherent Organizational Identity in Order to Organizational Capacity Development of Universities in Hamedan - Mohammad Reza Ardalan; Siroos Ghanbari; Iman Karimi (جامعه شناسی کاربردی, 2016)
Introduction: Today the university as an effective organization can be, Organizational capacity development as a model of planned change to use Learn to solve problems, adapt to environmental changes, improve their performance and effectiveness in the future. In order to build capacity in universities must intangible assets such as organizational identity focused. organizational identity plays a central role in regulating the behavioral norms of the organization's members. The of finding identity, employees of the important characteristics as the characteristics they attract. The purpose of the present study organizational characteristics that affect organizational coherent identity to the basis for Organizational capacity development.Material & Methods: This research is based on the target application is based on a description of the method of data collection survey. The population of the city of Hamadan University research represents all employees, Sample using Cochran's formula for infinite population, 392 employees randomly from four universities in the city of Hamedan (Bu Ali Sina, Medical Sciences, industrial, Islamic Azad) were selected. Data collection questionnaires organizational characteristics With 29 Question, corporate identity With 8 Question and organizational capacities With 22 Question were evaluated. Cronbach's alpha coefficient, to assess the reliability of the questionnaire was at an acceptable level above 0/90. Data analysis using confirmatory factor analysis and structural equation modeling using LISREL and SPSS software was used.Discussion of Results & Conclusions: Confirmatory factor analysis results showed all factor loadings (Î») obtained the obvious variables, are statistically significant at the %5 error level. It is obvious that variables fitness model acceptable to measure structures were hidden. Analysis results show that the structural relationships; the effect of a coherent strategy is on the corporate identity of (0/90) considering the significant amount of T statistic at %5 the first hypothesis that the positive impact of the strategy on corporate coherent identity is confirmed. The effect of other variables affecting coherent corporate identity in order to is, Tools and support (0/86), quality management (0/83), internal communications (0/87), openness and dynamism (0/79), Considering the significant amount of relevant statistic T to each of them at the level of 5% error, Fourth and fifth hypothesis that the positive effects of other institutional factors affecting organizational identity verification are integrated. Coherent corporate identity in relation to the impact on cohesion, the positive effect is of (0/94), considering the significant statistics at %5 T, Sixth hypothesis is confirmed. The effect of coherent identity to other organizational structures pave the way for the development of institutional capacity is in order to, Informal communication (0/87), the centralization (0/79), feedback-control system (0/84) and organizational performance (0/80) Considering the significant amount of relevant statistic T to each of them at the level of 5% error, The seventh to the tenth of a coherent identity hypothesis positive impact on other organizational structures organizational capacity will be verified. Finally, the index values of the goodness of fit of the structural model research all were acceptable limits. This shows that good research model fitted to the data or the is structural model. Therefore say the results of the activities of the staff to achieve the goals described in terms of organization and social activities, can be effective in enhancing the identification of employees. In addition, increasing staff participation in organizational decision and enhance the sense of responsibility and staff Encourage responsibility for their orientation through a fair reward system will be facilitates access to the development of institutional capacity. Accordingly, the organization of the coherent identity is more important, access to opportunities and conditions for the development of organizational capacity will be easier.